Review of experience in the construction of NPP using modular structures with external sheet reinforcement - D. N. Korotkikh; O. A. Kornev; V. V. Belov; A. S. Silantiev; D. E. Kapustin (Vestnik MGSU)
Introduction. To increase the competitiveness of domestic NPP projects, it is necessary to reduce the construction time to 36 months. One of the ways to solve this problem is industrialization of the construction process, which uses prefabricated elements in the form of volumetric units with sheet steel cladding. The paper reviews open sources of information on the experience of erecting nuclear power plants using modular reinforced concrete structures with external sheet reinforcement. The following projects were considered: AR-1000 by Westinghouse (USA) and ATS-1000 (SNERDI).Materials and methods. On the basis of analysis, generalization and systematization of information obtained from open sources, the authors reviewed the practical experience of application of structures with external sheet reinforcement in the construction of NPP (under the AP-1000 and CAP-1000 projects) at the following facilities: Sanmen, Haiyang, Xudabao and Lianjiang (China), V.C. Summer and Vogle (USA).Results. The main method of erection in the implementation of NPP projects using modular reinforced concrete structures with external sheet reinforcement was the erection of extra-large units using the open-top technology. The use of such technology imposes higher requirements to the design documentation, manufacturing of unit modules requires strict control of logistic risks. Lack of quality control methods for compaction of monolithic concrete placed in the structure increases the requirements to the quality of concrete mixtures and technology of their placement.Conclusions. In general, the technology of modular construction using reinforced concrete structures with external sheet reinforcement allows to significantly reduce labor costs of erecting structures directly on the construction site. However, based on the results of analyzing the experience of implementation of AR-1000 and SAR-1000 design solutions, it was found that additional logistical risks and risks of ensuring the quality of monolithic concrete placement arise when implementing this technology.